Can Exercise Increase Fitness and Reduce Weight in Patients with Schizophrenia and Depression? - Krogh, Jesper; Speyer, Helene; Nørgaard, Hans Christian Brix; Moltke, Ane; Nordentoft, Merete (Frontiers in Psychiatry, 2014)
Background Psychiatric patients have a reduced life expectancy of 15 to 20 years compared to the general population. Most years of lost life are due to excess mortality from somatic diseases. Sedentary lifestyle and medication is partly responsible for the high frequency of metabolic syndrome in this patient group and low levels of physical activity is associated with increased risk of cardiovascular disease, diabetes and all-cause mortality. This study aimed to review trials allocating patients with either schizophrenia or depression to exercise interventions for effect on cardiovascular fitness, strength and weight. Methods We searched Pubmed, Embase, and Psycinfo including randomized clinical trial allocating patients with either schizophrenia or depression to isolated exercise interventions. Results We identified five trials including patients with schizophrenia and found little evidence that exercise could increase cardiovascular fitness or decrease weight. Nine exercise trials for patients with depression were identified increasing cardiovascular fitness by 11-30% and strength by 33-37%. No evidence in favor of exercise for weight reduction was found. Conclusion Based on the current evidence isolated exercise interventions are unlikely to improve cardiovascular fitness or induce weight loss in patients with schizophrenia. In patients with depression exercise interventions are likely to induce clinically relevant short term effects, however, due to lack of reporting little is known about the effect on cardiovascular fitness beyond the intervention and weight reduction. Future exercise trials regarding patients with mental illness should preferably measure changes in cardiovascular strength, repetition maximum and anthropometric outcomes. Ideally participants should be assessed beyond the intervention